Development of Digital Teaching Materials Based on Google Slide Pear Deck in Water Cycle Process Material In Elementary School - Siswanto, Siswanto; Supriyanto, Teguh; Anam, Rifat Shafwatul (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
The development of digital-based teaching materials is significant in today's digital era. However, a few elementary school teachers could still improve at developing digital teaching materials, including teaching materials based on Google Slide Pear Deck. Teachers have carried out several developments. However, only some still need to focus on developing digital teaching materials based on Google Slide Pear Deck on science materials in elementary schools. This research aims to produce digital teaching materials with Google Slide Pear Deck that are valid, practical, and effective. This type of research is development research with the ADDIE model (Analyze, Design, Develop, Implementation, Evaluation). Data collection instruments are tests, questionnaires, interview sheets, and observations. Based on the results of the analysis and discussion of the research data, it is obtained that the digital teaching materials based on Google Slide Pear Deck are a media in class V semester 1 with the subject matter of the water cycle process has met the criteria of valid, practical and effective, so that this teaching material is suitable for use as a medium to increase interest and learning outcomes of science material on the water cycle process. Further research needs to be carried out to complement the shortcomings of this research, especially in developing teaching materials based on Google Slide Pear Deck, which raises a variety of subject matter in elementary schools.